TINGKAT KEKAKUAN PADA BETON BERTULANG MENGGUNAKAN APLIKASI RESPONSE-2000 - Fanny Monika; Hakas Prayuda; Al Fajir M Sarita (Prodi Teknik Sipil FT Universitas Sebelas Maret, 2019)
The behavior of precast concrete beams can be seen in the magnitude of the value of maximum load, deflection, moment and curvature. To facilitate analyzing these parameters using the Response-2000 software. The software is used to analyze beams with evenly distributed loads. The output of the application is in the form of deflection values, maximum load, and moment of curvature. This research was carried out by varying the dimensions of the beam and the position of the flexural reinforcement with a span length of 10 m. BU3 beam with a height of 1000 mm, width 150 mm, upper wing height 160 mm, lower wing height 150 mm upper wing width 300 mm and lower wing height 450 mm has a deflection of at least -95,248 mm and BU6 beam with a height of 1080 mm, width 152 mm, wing height 100 mm, wing height 130 mm, wingspan 381 mm and wing width 508 mm having a deflection of at most -114,471 mm. BU2 beam with a height1000 mm, width 150 mm, upper wing height 240 mm, wing height 150 mm, wingspan 300 mm and wingspan 450 mm has the smallest maximum load 81,265 kN/m and BU6 beam has maximum load 93,224 kN/m. BU2 beam has the smallest nominal moment of 1821,036 kNm and BU6 beam has the largest nominal moment value of 2093,920 kNm